Efficient N-Glycosylation of the Heavy Chain Tailpiece Promotes the Formation of Plant-Produced Dimeric IgA - Göritzer, Kathrin; Goet, Iris; Duric, Stella; Maresch, Daniel; Altmann, Friedrich; Obinger, Christian; Strasser, Richard (Frontiers in Chemistry, 2020)
Production of monomeric IgA in mammalian cells and plant expression systems such as Nicotiana benthamiana is well established and can be achieved by co-expression of the corresponding light and heavy chains. In contrast, the assembly of dimeric IgA requires the additional expression of the joining chain and remains challenging especially in plant-based systems. Here, we examined factors affecting the assembly and expression of HER2 binding dimeric IgA1 and IgA2m(2) variants transiently produced in N. benthamiana. While co-expression of the joining chain resulted in efficient formation of dimeric IgAs in HEK293F cells, a mixture of monomeric, dimeric and tetrameric variants was detected in plants. Mass-spectrometric analysis of site-specific glycosylation revealed that the N-glycan profile differed between monomeric and dimeric IgAs in the plant expression system. Co-expression of a single-subunit oligosaccharyltransferase from the protozoan Leishmania major in N. benthamiana increased the N-glycosylation occupancy at the C-terminal heavy chain tailpiece and changed the ratio of monomeric to dimeric IgAs. Our data demonstrate that N-glycosylation engineering is a suitable strategy to promote the formation of dimeric IgA variants in plants.